Klasifikasi Beras Menggunakan Metode K-Means Clustering Berbasis Pengolahan Citra Digital - Atriyan Trisnawan; Wahyudi Hariyanto; Syahminan - (Fakultas Sains & Teknologi Universitas Kanjuruhan Malang, 2019)
Rice plants (Oryza Sativa L.) are important food crops that have become a staple food for more than half of the world's population. In Indonesia rice is the main commodity in supporting community food. The process of processing rice into rice is done in two ways, namely the processing of pulverized and modern processing using a grinding tool. Rice is an important component in daily food. There are several types on the market, namely: fragrant pandan rice, IR 64, IR 42, C 4, and others. With the variety of forms and types of rice on the market, there are many weaknesses that humans have in perceiving the classification of rice using the senses of vision. Therefore, digital image processing techniques are needed to help analyze the type of rice. This study aims to analyze the type of rice using the K-Means Clustering method based on RGB colors. Before the K-Means calculation, the RGB color feature extraction process must be carried out to get the red value, green value, blue value in each image. The results of this study found that image processing to determine the type of rice using the k-means clustering method can help users to know the type of rice.